2007
DOI: 10.1093/ps/86.8.1625
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Fiber and Reduced Crude Protein on Ammonia Emission from Laying-Hen Manure

Abstract: Ammonia (NH(3)) emission is a major concern for the poultry industry. The objective of this research was to determine whether inclusion of dietary fiber and a reduced dietary CP content would decrease NH(3) emission from laying-hen manure. A total of 256 Hy-Line W-36 hens were fed diets with 2 levels of CP (normal and reduced) and 4 fiber treatments in a 2 x 4 factorial arrangement. The fiber treatments included a corn and soybean meal-based control diet and diets formulated with either 10.0% corn dried distil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 30 publications
4
39
0
6
Order By: Relevance
“…The relationship between birds' diet and excreted nitrogen contents has been widely studied. While Summers et al (1993) and Roberts et al (2007) successfully reduced the amount of excreted nitrogen by diet manipulations, claimed no significant effects of crude protein percentage in diet on the amount of total N and uric acid-N in fresh litter of layer hens. Manure removal strategy determined both the amount and the surface area of manure remaining in the pit.…”
Section: Managerial Parametersmentioning
confidence: 96%
“…The relationship between birds' diet and excreted nitrogen contents has been widely studied. While Summers et al (1993) and Roberts et al (2007) successfully reduced the amount of excreted nitrogen by diet manipulations, claimed no significant effects of crude protein percentage in diet on the amount of total N and uric acid-N in fresh litter of layer hens. Manure removal strategy determined both the amount and the surface area of manure remaining in the pit.…”
Section: Managerial Parametersmentioning
confidence: 96%
“…Dietary fiber has been shown to cause a decrease in manure pH and decrease uric acid-N excretion with a concurrent decrease in NH 3 emissions. Roberts et al (2007a) fed laying hens diets that contained 10.0% corn distiller's dried grains with solubles, 7.3% wheat middlings, or 4.8% soybean hulls. The NH 3 emission from the laying-hen manure was decreased 41%, 38%, and 27% for the corn distiller's dried grains with solubles, wheat middlings, and soybean hulls, respectively (Roberts et al, 2007a).…”
Section: Dietary Fibermentioning
confidence: 99%
“…Roberts et al (2007a) fed laying hens diets that contained 10.0% corn distiller's dried grains with solubles, 7.3% wheat middlings, or 4.8% soybean hulls. The NH 3 emission from the laying-hen manure was decreased 41%, 38%, and 27% for the corn distiller's dried grains with solubles, wheat middlings, and soybean hulls, respectively (Roberts et al, 2007a). No repartitioning of N excretion could be detected in the study but manure pH was decreased from 7.08 for the control-fed hens to 6.77, 6.80, and 6.85, respectively, for the hens fed corn distiller's dried grains with solubles, wheat middlings, and soybean hulls (Roberts et al, 2007a).…”
Section: Dietary Fibermentioning
confidence: 99%
“…On-site filter efficiency is summarized in Chapter 3. Roberts et al, 2007;Wu-Haan et al, 2007;, Roberts et al, 2009. Amino acids supplied above the level of the limiting amino acid cannot be used and the nitrogen is excreted.…”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…Also, the higher supply of DDGS in animal diets, because of the rapid increase in production of ethanol encourages comparison (Waldroup et al, 2007). Roberts et al (2007) found a reduction of approximately 40% in NH 3 emission from manure of laying hens fed 10% dietary DDGS. In spite of the MAEMU"s precision and real-time measurement capabilities, its relative immobility and high cost limits the widespread use for baseline emission and mitigation studies.…”
Section: Introductionmentioning
confidence: 99%